The impact of innovation on economic growth, foreign direct investment, and self-employment: A global perspective - Juan Dempere; Muhammad Ali Jibran Qamar; Hesham Allam; Sabir Malik (Economies, 2023)
This paper aims to investigate the impact of innovation on three macroeconomic indicators: GDP, self-employment, and foreign direct investment (FDI). The study analyses a sample of 120 countries using the Global Innovation Index (GII) and its constituent sub-indices and pillars, which provide a holistic evaluation of national innovation. Gross domestic product (GDP) per capita measures a country's economic output, self-employment assesses entrepreneurial activity, and FDI indicates confidence in a country's economic prospects and innovation trends. This study analyzes the data using generalized-linear and panel-corrected standard-error models. The results show that innovation positively influences GDP, domestic institutional framework, local infrastructure, local knowledge and technology, and creative outputs. In contrast, innovation negatively correlates with domestic self-employment, often associated with necessity-driven entrepreneurship. The study concludes that innovation positively affects human resources, research, and creative outputs and has no significant impact on FDI. The findings suggest that a practical regulatory framework, institutional support, domestic human capital, research and development, infrastructure, technology, and creative outputs are essential for a vibrant economy. National innovation policies supporting the GII and its constituent factors can positively affect the economy while reducing self-employment.
Keywords: 330; innovation; FDI; entrepreneurship; Global Innovation Index; self-employment; foreign direct investment; economic growth; GDP; creative outputs; globalization